2020
DOI: 10.3233/jpd-191841
|View full text |Cite
|
Sign up to set email alerts
|

EASE LID 2: A 2-Year Open-Label Trial of Gocovri (Amantadine) Extended Release for Dyskinesia in Parkinson’s Disease

Abstract: Background: Gocovri ® (amantadine) extended release capsules are approved for the treatment of dyskinesia in patients with Parkinson's disease (PD) receiving levodopa-based therapy. Objective: To evaluate the long-term safety, tolerability, and efficacy of Gocovri in patients with PD experiencing levodopainduced dyskinesia. Methods: In this 2-year open-label trial, patients completing double-blind Gocovri clinical trials or excluded from prior trials because of deep-brain stimulation (DBS) received Gocovri 274… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 23 publications
(46 reference statements)
0
25
0
Order By: Relevance
“…The drug underwent a final 2-year open-label trial in 223 PD patients with LID and showed long-term safety, tolerability, and efficacy on dyskinesia and OFF time. 107 However, the drug is not available outside the US.…”
Section: Experimental Pharmacological Therapies For Lid In Pd Patientsmentioning
confidence: 99%
“…The drug underwent a final 2-year open-label trial in 223 PD patients with LID and showed long-term safety, tolerability, and efficacy on dyskinesia and OFF time. 107 However, the drug is not available outside the US.…”
Section: Experimental Pharmacological Therapies For Lid In Pd Patientsmentioning
confidence: 99%
“…In the longer EASE LID study, treatment benefits in increasing ON time without troublesome dyskinesia, and reducing OFF time, time spent ON with troublesome dyskinesia and with dyskinesia (troublesome + non-troublesome) were maintained and were all significantly different than placebo (all p < 0.05) among those patients who completed the entire 24 weeks of treatment (before the study was prematurely stopped to allow regulatory filing) ( 14 ). Recent analyses of the open-label EASE-LID 2 study further showed maintenance of benefits in terms of reducing ON time with dyskinesia and OFF time (as assessed by the MDS-UPDRS Part IV) over 2 years ( 28 ). Finally, while patients in the trial had to have peak-dose dyskinesia, other forms of dyskinesia were not excluded, and combinations of choreic and dystonic movements, peak-dose and end-of-dose dyskinesias often occur in the same patient.…”
Section: Discussionmentioning
confidence: 99%
“…The amantadine ER(Go) development programme included non-clinical toxicology studies to meet current standards, and pharmacokinetic studies, in addition to the following clinical studies: the phase II/III EASED study (Extended release Amantadine Safety and Efficacy study in levodopainduced Dyskinesia), which was a dose-finding study; 59 the pivotal EASE LID and EASE LID 3 studies (Extended release Amantadine Safety and Efficacy studies in Levodopa-Induced Dyskinesia); 40,41 and the 2-year, open-label EASE LID 2 study. 60 An overview of these studies is included in Table 1.…”
Section: The Amantadine Extended-release Gocovri Clinical Development Programmementioning
confidence: 99%